2012
DOI: 10.5402/2012/785094
|View full text |Cite
|
Sign up to set email alerts
|

New Alternatives for Atherosclerosis Treatment Based on Immunomodulation

Abstract: Atherosclerosis and its derived cardiovascular diseases are a leading cause of death in the western world. The treatment of atherosclerosis is currently based on lipid lowering in combination with anti-inflammatory therapies that slow the progression of atherosclerosis. Still, these therapies are not able to fully inhibit the formation or progression of atherosclerotic lesions. Ever since it was first demonstrated that the immunological system plays an important role during atherogenesis, various different imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Antibody levels against HSP60/65 are increased in subjects with cardiovascular disease and are associated with disease outcome. Different vaccination protocols based on these proteins protect against progression of early atherosclerosis by inducing Treg activation [95, 96]. Recently, we suggested that human HSP90 is a possible autoantigen involved in the pathogenesis of carotid atherosclerosis [97].…”
Section: Antigens Inducing T Lymphocyte Activation In Atherosclerosismentioning
confidence: 99%
“…Antibody levels against HSP60/65 are increased in subjects with cardiovascular disease and are associated with disease outcome. Different vaccination protocols based on these proteins protect against progression of early atherosclerosis by inducing Treg activation [95, 96]. Recently, we suggested that human HSP90 is a possible autoantigen involved in the pathogenesis of carotid atherosclerosis [97].…”
Section: Antigens Inducing T Lymphocyte Activation In Atherosclerosismentioning
confidence: 99%